(untitled) (GnosisWisdom, 2022)
Objective: to determine the truth or lie of the benefits of coca in the treatment of malnutrition and anemia. Materials and methods: It used the type of quantitative research of descriptive level, theoretical, deductive, empirical method, of non-experimental design, it had an analysis sample of 100 gr of coca flour, it used the technique of SMEWW Method 3133B. 23rd Edition 2017. Direct Air - Acetylene Flame Method and AAS * method performed in 2 laboratories. Results: UNH laboratory. calcium (Ca) 26.81mg/kg and Iron (Fe) 73.7mg/kg; UNMSM laboratory, Calcium (Ca) 780.83 mg/100g, Iron (Fe) 49.46 mg/100g, Proteins 2.71%: ULM laboratory, Calcium (Ca) 10657.5mg/kg, Iron (Fe) 117.5mg/kg, protein 16.5. Conclusions: it is true that the coca leaf has nutrients to be used in the treatment of malnutrition and anemia.